Influence of ionizing radiation and cell density on the kinetics of autocrine destruction and intercellular induction of apoptosis in precancerous cells - Abdelrazzak, AB; O’Neill, P; Hill, MA (Springer Nature, 2022)
Intercellular induction of apoptosis (IIA) represents a well-defned signaling model by which precancerous cells are selectively eradicated through reactive oxygen/nitrogen species and cytokine signaling from neighbour normal cells. Previously, we demonstrated that the IIA process could be enhanced by exposure of normal cells to very low doses of ionizing radiation as a result of perturbing the intercellular signaling. In this study, we investigate the kinetic behaviour of both autocrine destruction (AD) and IIA as a function of cell density of both precancerous and normal cells using an insert co-culture system and how exposure of normal cells to ionizing radiation infuence the kinetics of apoptosis induction in precancerous cells. Increasing the seeding density of transformed cells shifts the kinetics of AD towards earlier times with the response plateauing only at high seeding densities. Likewise, when co-culturing precancerous cells with normal cells, increasing the seeding density of either normal or precancerous cells also shifts the kinetics of IIA response towards earlier times and plateau only at higher seeding densities. Irradiation of normal cells prior to co-culture further enhances the kinetics of IIA response, with the degree of enhancement dependent on the relative cell densities. These results demonstrate the pivotal role of the cell seeding density of normal and precancerous cells in modulating both AD and IIA. These results further support the proposition that ionizing radiation could result in an enhancement in the rate of removal of precancerous cells through the IIA process.